Designing and development of a rechargeable screwdriver for assembly project - Mohd Din, Yusuff Badrisyah; Mohd Yusof, Ab Aziz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This project introduces an automatic rechargeable screwdriver, designed to assist people in assembling and disassembling various items like cupboards, tables, and chairs. The screwdriver operates through rotational motion powered by a DC rotary motor, enabling users to tighten or loosen screws as needed. Consideration for sustainability is a key focus of this project. Materials chosen for the product prioritize affordability and usability, with an emphasis on recyclable and reusable components. The aim is to make the screwdriver accessible to people of all ages, from youngsters to seniors, ensuring its usability across generations. The authors also evaluate the advantages and disadvantages of the screwdriver, particularly in terms of sustainability, primary functionality, and versatility. Notably, the screwdriver's design allows for easy interchangeability of tips to accommodate different screw sizes. Overall, the project aims to create a fully functional screwdriver that simplifies the task of tightening and loosening screws with a simple flip of a switch, catering to the diverse needs of users across various age groups.